Hyperinflammation in COVID-19 Obese Patients Treated With Tocilizumab: A Successful Case Series - Beatriz Amorim Beltrão RN, PhD; Rafael Cabral Teixeira MD; Diego Bastos Porto MD, MSc (SAGE Publishing, 2021)
The cytokine storm syndrome has been suggested as a mechanism in the pathophysiology of SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2; COVID-19 [coronavirus disease 2019]) infection. Drugs such as tocilizumab, an interleukin-6 antagonist, have shown good results in other scenarios of hyperinflammatory state and might also be effective in COVID-19 disease. However, the best dosing regimen and the timing of infusion is currently unknown, specifically in obese patients. We report the first cases of tocilizumab administration in obese patients during the first days of COVID-19 worsening hypoxemia. This infusion was not adjusted by weight, following the manufacturer maximal dose limit. We kept a strict monitoring for possible infections, prior and during the treatment. All patients showed good improvements on chest-computed tomography images and oxygenation and were discharged from hospital shortly after, without complications or intubation. This case series highlights that tocilizumab seems to be effective to treat hyperinflammation of critical COVID-19 obese patients, even when the infusion of the ideal dose is not feasible to be administered. It also shows the importance of early timing in the decision to treat and the relevance of infections exclusion prior to the induction of immunosuppression by tocilizumab.